MENINGKATKAN MINAT BELAJAR GEOGRAFI PADA MATERI POSISI STRATEGIS INDONESIA KELAS XI DI SMA NEGERI 1 GAROGA - Esti Sastina Hutabarat; Sugiharto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to: (1) describe the development of AI-based learning media on the topic of Indonesia’s strategic position, (2) examine the feasibility of the developed media, and (3) analyze its effectiveness in improving students’ interest and learning outcomes. The research method employed was Research and Development (R&D) using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were 34 students of class XI IPS 1. The validation results indicate that the AI-based learning media developed falls into the category of highly feasible in terms of content, language, and presentation. The use of this media proved effective in enhancing students’ learning interest, where prior to its use, most students were in the low-interest category, while after its implementation, all students were in the high to very high category. Furthermore, learning outcomes showed a significant improvement; the average pretest score of 53.38 increased to 90.44 in the posttest, with no students scoring below the minimum mastery criteria (KKM). Therefore, the development of AI-based learning media has been proven to be feasible and effective in improving both learning interest and outcomes in Geography subjects. This research recommends that teachers utilize AI-based media as an innovative alternative in teaching and that schools support its implementation by providing adequate technological facilities.